2018
DOI: 10.1139/cjfas-2017-0406
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic telemetry observation systems: challenges encountered and overcome in the Laurentian Great Lakes

Abstract: The Great Lakes Acoustic Telemetry Observation System (GLATOS), organized in 2012, aims to advance and improve conservation and management of Great Lakes fishes by providing information on behavior, habitat use, and population dynamics. GLATOS faced challenges during establishment, including a funding agency-imposed urgency to initiate projects, a lack of telemetry expertise, and managing a flood of data. GLATOS now connects 190+ investigators, provides project consultation, maintains a web-based data portal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 43 publications
0
67
0
Order By: Relevance
“…Even with great investments in telemetry science, there is still a lack of documentation and assessment of the conservation impact of telemetry research (Jeffers andGodley 2016, Mcgowan et al 2016). Hesitation and delay in applying telemetry-derived data to fisheries management have also been reported for reasons such as uncertainties associated with telemetry studies, limitations of the technology, unknown effects on tagged animals, distrust of telemetry (reliability and credibility issues), mismatches between management needs and design of telemetry studies (e.g., compatibility, representativeness, timeliness), or lack of awareness and access to new findings , Young et al 2013, 2018, Crossin et al 2017Nguyen et al, 2018a,b). It has also been suggested that publications are too focused on research results rather than on conservation and management implications, and that the recommendations put forth lack context and are not readily useable by decision makers (Roux et al 2006).…”
Section: Context: Telemetry Science and Fisheries Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with great investments in telemetry science, there is still a lack of documentation and assessment of the conservation impact of telemetry research (Jeffers andGodley 2016, Mcgowan et al 2016). Hesitation and delay in applying telemetry-derived data to fisheries management have also been reported for reasons such as uncertainties associated with telemetry studies, limitations of the technology, unknown effects on tagged animals, distrust of telemetry (reliability and credibility issues), mismatches between management needs and design of telemetry studies (e.g., compatibility, representativeness, timeliness), or lack of awareness and access to new findings , Young et al 2013, 2018, Crossin et al 2017Nguyen et al, 2018a,b). It has also been suggested that publications are too focused on research results rather than on conservation and management implications, and that the recommendations put forth lack context and are not readily useable by decision makers (Roux et al 2006).…”
Section: Context: Telemetry Science and Fisheries Managementmentioning
confidence: 99%
“…Research networks offer an opportunity to expand this research, given that they often include both scientists and practitioners. For example, the Great Lakes Fishery Commission and its associated Great Lakes Acoustic Telemetry Observation System (network of telemetry researchers) make up a community of both science and practice (Krueger et al 2018). Evaluating the various cases that have derived from Great Lakes fisheries research using telemetry could be a viable method to get to a truer measure of "successful" knowledge outcomes.…”
Section: Application Of Findings and Future Researchmentioning
confidence: 99%
“…The design of a network is a challenging task primarily because the deployment and maintenance of expansive acoustic receiver networks may be beyond the capabilities of most single organizations, and thus requires interagency coordination. Consortiums and organizations, such as the Great Lakes Acoustic Telemetry Observation System (GLATOS; http://glatos.glos.us/, Krueger et al., ), Integrated Marine Observing System (IMOS; http://imos.org.au/home/) and the Ocean Tracking Network (OTN; Cooke et al., ), are becoming increasingly important for the success of acoustic telemetry studies, but this enterprise requires compromise in the sampling design to manage financial resources and achieve a network that will function for multiple objectives and species. Studies initiated after a network is established will be forced to consider whether the existing array addresses the objective(s) or whether augmentation of the network would be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Detections from VR2W receivers ( n = 343 unique stations), including those not directly associated with this work, were retrieved from the Great Lakes Acoustic Telemetry Observation System (GLATOS; https://glatos.glos.us; Krueger et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Range to 90% detection probability was estimated at 635 m (D. Hondorp, unpublished data), so sturgeon in the Detroit and St. Clair rivers (channel width 300-900 m; Tables 1 and 2) were unlikely to pass individual receivers undetected. Detections from VR2W receivers (n = 343 unique stations), including those not directly associated with this work, were retrieved from the Great Lakes Acoustic Telemetry Observation System (GLATOS; https://glatos.glos.us; Krueger et al 2018).…”
Section: Fish Collection and Acoustic Monitoringmentioning
confidence: 99%